Impact of the COVID-19 pandemic on antidepressant prescribing with a focus on people with learning disability and autism: an interrupted time series analysis in England using OpenSAFELY-TPP - Ben Goldacre; David Evans; Orla Macdonald; Richard Croker; Rebecca Smith; Christopher Wood; Andrea Schaffer; Andrew Brown; Brian MacKenna; William Hulme; Chris Bates; Amir Mehrkar; et al. (BMJ Mental Health)
Background COVID-19 restrictions led to increased reports of depressive symptoms in the general population and impacted health and social care services. We explored whether these changes affected antidepressant prescribing trends in the general population and those with learning disability or autism.Methods With the approval of NHS England, we used >24 million patients’ primary care data from the OpenSAFELY-TPP platform. We used interrupted time series analysis to quantify trends in those prescribed and newly prescribed an antidepressant across key demographic and clinical subgroups, comparing pre-COVID-19 (January 2018–February 2020), COVID-19 restrictions (March 2020–February 2021) and recovery (March 2021–December 2022) periods.Results Prior to COVID-19 restrictions, antidepressant prescribing was increasing in the general population and in those with learning disability or autism. We did not find evidence that the pandemic was associated with a change in antidepressant prescribing trend in the general population (relative risk (RR) 1.00 (95% CI 0.97 to 1.02)), in those with autism (RR 0.99 (95% CI 0.97 to 1.01)) or in those with learning disability (RR 0.98 (95% CI 0.96 to 1.00)).New prescribing post restrictions was 13% and 12% below expected had COVID-19 not happened in both the general population and those with autism (RR 0.87 (95% CI 0.83 to 0.93), RR 0.88 (95% CI 0.83 to 0.92)), but not learning disability (RR 0.96 (95% CI 0.87 to 1.05)).Conclusions and implications In this England study, we did not see an impact of COVID-19 on overall antidepressant prescribing, although unique trends were noted, such as trends in new antidepressant prescriptions which increased in care homes over the pandemic and decreased in the general population and those with autism since recovery.